2019
DOI: 10.24061/2413-4260.ix.2.32.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Preterm Neonates: Perinatal Risk Factors

Abstract: Вищий державний навчальний заклад України «Буковинський державний медичний університет» (м. Чернівці, Україна) ГОСТРЕ ПОШКОДЖЕННЯ НИРОК У ПЕРЕДЧАСНО НАРОДЖЕНИХ ДІТЕЙ: ПЕРИНАТАЛЬНІ ЧИННИКИ РИЗИКУ Резюме Вступ. Гостре пошкодження нирок (ГПН) є одним з найбільш загрозливих проявів синдрому поліорганної недостатності у новонароджених критично хворих дітей, особливо за умов їх передчасного народження. Частота діагностування ГПН у пацієнтів відділень інтенсивної терапії новонароджених складає від 18 до 70 %. ГПН у н… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…One of the threatening pathological conditions contributing to a high incidence and mortality rate in perinatal pathology among preterm infants (PTIs) is acute kidney injury (AKI), with a frequency ranging from 25 to 56 % within this infant cohort [1][2][3]. Various studies have demonstrated that the epidemiology of renal dysfunction in children has signifi cantly evolved over the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…One of the threatening pathological conditions contributing to a high incidence and mortality rate in perinatal pathology among preterm infants (PTIs) is acute kidney injury (AKI), with a frequency ranging from 25 to 56 % within this infant cohort [1][2][3]. Various studies have demonstrated that the epidemiology of renal dysfunction in children has signifi cantly evolved over the past few decades.…”
Section: Introductionmentioning
confidence: 99%